For this case we have the following function:
![f (x) = - 3x ^ 2 + 4x + 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8wxqbbcg7ypl58j00jnyn0lj72b74mjx8s.png)
We must evaluate the function when
and
![x = 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/gn0ewdpib9ooyfthsjwp8oi4900vxj88n6.png)
For
:
![f (2) = - 3 (2) ^ 2 + 4 (2) +6\\f (2) = - 3 * 4 + 8 + 6\\f (2) = - 12 + 8 + 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9ovddrljq52cn1jbiypftw5tpralq1e1i8.png)
Different signs are subtracted and the major sign is placed.
Equal signs are added and the same sign is placed.
![f (2) = - 4 + 6\\f (2) = 2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/stvdzrbwrbh5uns5pev3ubf1sv8j5gfary.png)
For
:
![f (3) = - 3 (3) ^ 2 + 4 (3) +6\\f (3) = - 3 * 9 + 12 + 6\\f (3) = - 27 + 12 + 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c3d2ybesh1pktqga2nsv86sudagv1whfju.png)
Different signs are subtracted and the major sign is placed.
Equal signs are added and the same sign is placed.
![f (3) = - 15 + 6\\f (3) = - 9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5xpmo1wckmjud7058as3ab4eovql9cbiyn.png)
Answer:
![f (2) = 2\\f (3) = - 9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ile64ta6l4og8vx6fdebnkxhcp7zhfcd47.png)